2012
DOI: 10.1085/jgp.201110692
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of the taper of vertebrate cone photoreceptors

Abstract: Vertebrate photoreceptors are commonly distinguished based on the shape of their outer segments: those of cones taper, whereas the ones from rods do not. The functional advantages of cone taper, a common occurrence in vertebrate retinas, remain elusive. In this study, we investigate this topic using theoretical analyses aimed at revealing structure–function relationships in photoreceptors. Geometrical optics combined with spectrophotometric and morphological data are used to support the analyses and to test pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 241 publications
(228 reference statements)
1
34
0
Order By: Relevance
“…In contrast, migrations to new environments do not induce changes in cone outer segment morphology (e.g. size, taper) in salmonid fishes, and we are not aware of reports to the contrary for other animals featured in the literature (Hárosi and Novales Flamarique, 2012). It thus seems that the reported phenotypic plasticity in opsin expression of fishes is probably based on changes in the relative numbers of spectral cone types.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In contrast, migrations to new environments do not induce changes in cone outer segment morphology (e.g. size, taper) in salmonid fishes, and we are not aware of reports to the contrary for other animals featured in the literature (Hárosi and Novales Flamarique, 2012). It thus seems that the reported phenotypic plasticity in opsin expression of fishes is probably based on changes in the relative numbers of spectral cone types.…”
Section: Introductionmentioning
confidence: 67%
“…At the ellipsoid level, single and double cones formed square mosaics in the ventral retina (Fig.5G) and mostly row mosaics in the rest of the retina (Fig.5D). As is the case for the majority of fish species that have been studied (see Hárosi and Novales Flamarique, 2012), the square mosaic unit of the threespine stickleback consisted of four double cones forming a square, or cruciform, arrangement and a variable number of single cones, from 1 to 5 (Fig.5A-C,G-I). Single cones were predominantly central in the mosaic unit, at the hypothetical intersection of neighbouring double cone partitions (Novales Flamarique, 2001;Cheng et al, 2006), but a few corner cones could also be found in the central and centro-dorsal areas of the retina (Fig.5A,B).…”
Section: Cone Mosaics and Distributions Of Opsinsmentioning
confidence: 94%
See 1 more Smart Citation
“…Enlarged, rod-like outer segments are known to increase sensitivity by increasing cell volume and, as a result, the number of visual pigment molecules available to catch photons (3,34). Recent theoretical work has proposed that the small tapering outer segments of cones may help to reduce self-screening of the visual pigments, increase signal-to-noise ratios, and allow light to more efficiently be focused on the outer segment by the ellipsoid (35). Interestingly, recent work has also suggested that reduction of RH1 expression alone can result in a more cone-like morphology, decreasing the photosensitivity of the cell and increasing the kinetics of the phototransduction cascade (34,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the optical properties of photoreceptor cells which, by geometry of the outer segment alone, "compensate for self-screening of the visual pigments" and/or for a "signal-to-noise ratio decline along the longitudinal dimension" (Hárosi and Novales Flamarique, 2012) will remain a fascinating research objective. Introducing megamitochondria into this field as a new mosaic piece has inspired the search for other organelles which are placed in the optic pathway and which may have an influence on the incoming light.…”
Section: "Lens Mitochondria" In the Cone Inner Segmentsmentioning
confidence: 99%